2010
DOI: 10.1159/000322896
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma with Extensive Nodularity Undergoing Post-Therapeutic Maturation to a Gangliocytoma: A Case Report and Literature Review

Abstract: We present a report of a 12-year-old boy diagnosed with medulloblastoma at 22 months of age. A gross total resection was performed followed by adjuvant systemic chemotherapy due to his young age; however, the tumor recurred locally in the posterior fossa 7 months later. The recurrent tumor was excised and he received craniospinal radiation with a boost given to the posterior fossa followed by high-dose chemotherapy. He remained disease free for approximately 10 years without major neurologic deficit and only m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The cells had small round to oval nuclei with mild to moderate hyperchromasia and minimal cytoplasm. This maturation can be either focal as described by Kudo et al 12 or Kubota et al 13 or near complete as in the cases reported by Cai et al 11 or Chelliah et al 14 Spontaneous maturation of medulloblastoma into ganglioglioma at diagnosis has also been reported. 15 Notably, 3 of these cases described tumors that were desmoplastic (or MBEN), whereas histology was unclear in the remaining 3.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…The cells had small round to oval nuclei with mild to moderate hyperchromasia and minimal cytoplasm. This maturation can be either focal as described by Kudo et al 12 or Kubota et al 13 or near complete as in the cases reported by Cai et al 11 or Chelliah et al 14 Spontaneous maturation of medulloblastoma into ganglioglioma at diagnosis has also been reported. 15 Notably, 3 of these cases described tumors that were desmoplastic (or MBEN), whereas histology was unclear in the remaining 3.…”
Section: Figurementioning
confidence: 78%
“…Desmoplastic medulloblastoma is more common in children younger than 3 years of age and has a better prognosis. 14 As in neuroblastoma, maturation of medulloblastoma cells may be associated with a better prognosis. 11 This case suggests that some types of medulloblastoma may have more potential for maturation, and research to identify the pathways that induce differentiation may facilitate the development of novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The data together indicated a medulloblastoma with maturation, a finding rarely documented in medulloblastomas. 81 A young child presented with an enhancing dura-based mass adjacent to the cerebellum. Upon resection, the lesion was confidently classified as a meningioma, and clear cell features were noted.…”
Section: Embryonal Cns Neoplasmsmentioning
confidence: 99%
“…Hemispheric tumors tend to arise in older patients (adolescents and young adults) many of these tumors are desmoplastic medulloblastomas [ 18 ] However, molecular advancements have revolutionized our understanding of these tumor well beyond their histopathology (see below). Rare cases of maturation of medulloblastoma after therapy have been reported [ 19 ].…”
Section: Medulloblastoma and Its Variantsmentioning
confidence: 99%
“…These areas contain streaming small cells resembling the cells of a central neurocytoma. Maturation into tumors dominated by ganglion cells has been reported [ 19 ].…”
Section: Medulloblastoma and Its Variantsmentioning
confidence: 99%